Factors Related to Unsafe Behaviour among Construction Workers: An Update Literature Review - Riky Suherman Simanjuntak; Chrismis Novalinda Ginting; Ali Napiah Nasution (Universitas Aisyah Pringsewu, 2023)
Construction become an hazardous occupation according to the unique nature of its activities commonly observed in the field. This review aims to delve into the risk factors of the unsafe actions on construction industry.The investigation involved analyzing findings from 16 relevant studies employing a qualitative content analysis procedure, variables, themes, and factors were extracted from the studies. Furthermore, all the studies underwent a review process to evaluate the result of the evidence provided. The content analysis revealed five categories: individual factors, project management, job characteristics, team dynamics, and stakeholders. The review emphasized that project management factors, such as organization, leadership, training,and procedure of working play a crucial role in minimizing the occurrence of unsafe behaviors. Additionally, individual factors emerged as the most significant risk factors of unsafe behaviour of workers including knowledge, perception, competency, psychology, and physical health. In conclusion, further research is needed to enhance the understanding of the relationship between theories of unsafe actions and empirical finding. Abstrak: Konstruksi dianggap sebagai pekerjaan berbahaya terutama karena sifat unik dari aktivitasnya yang biasa diamati di lapangan. Tinjauan ini bertujuan untuk menggali faktor-faktor yang mempengaruhi perilaku tidak aman pada industri konstruksi. Investigasi melibatkan analisis hasil dari 16 studi sebelumnya yang relevan menggunakan prosedur analisis konten kualitatif, variabel, tema, dan faktor diekstraksi dari studi. Selain itu, semua penelitian menjalani proses peninjauan untuk mengevaluasi kekuatan bukti yang diberikan. Analisis isi mengungkapkan lima kategori utama: faktor individu, manajemen proyek, karakteristik pekerjaan, kelompok kerja dan stakeholder. Tinjauan ini menekankan bahwa faktor managemen proyek sangat penting seperti organisasi, kepemimpinan, pelatihan dan prosedur kerja berkontribusi untuk meminimalkan terjadinya perilaku tidak aman. Selain itu, faktor individu menjadi faktor risiko terbanyak menciptakan perilaku tidak aman dalam bekerja seperti pengetahuan, persepsi, kompetensi, psikologi dan kesehatan fisik. Kesimpulannya, penelitian lebih lanjut perlu dilakukan untuk meningkatkan pemahaman tentang hubungan antara teori tindakan tidak aman dan temuan empiris.